Applications of Autonomous Underwater Vehicles in Offshore Petroleum Industry Environmental Effects Monitoring - Niu, H; Adams, S; K Lee; Husain, T; Neil Bose (2009)
Environmental Effects Monitoring (EEM) is an important tool in assisting Environmental Risk Assessment (ERA). EEM in the offshore petroleum industry has been conducted world wide, but traditional approaches have struggled to keep apace as exploration and production activities move to frontier regions, such as increasingly deeper waters and Arctic regions. This paper proposes the use of autonomous underwater vehicles (AUVs) for environmental monitoring of offshore facilities as a means of improving and expanding the overall monitoring program. The paper provides a review of technical and procedural issues involved in this application of AUV technology, including the current status of offshore oil and gas EEM, a review of available AUVs, and a survey of developments in in-situ sensors